NEUROENDOCRINE TUMOR AS A RARE CAUSE OF SMALL BOWEL ILEUS - Shumenkovski, Velimir; Arnaudov, Dimitar; Lokoski, Simon; Trajkovski, Gjorgji; Shumenkovska, Olga Pecakova; Shumkovski, Robert (Journal of Morphological Sciences; Vol 8 No 1 (2025): JMS, 2025)
Small bowel neuroendocrine tumors (SBNETs) are slow-growing neoplasms that have a tendency to metastasize and a relatively favorable prognosis. The presentation of Sb-NETs is diverse, although abdominal pain and obstructive symptoms are the most common symptoms. In patients with metastases, hypersecretion of serotonin and other bioactive amines results in carcinoid syndrome. Treatment of these tumors is multimodal and includes surgery, liver-directed therapy, somatostatin analogs, and peptide receptor radionuclide therapy. Keywords: neuroendokrine tumor, ileus.